Precise verbal feedback may speed the attainment of standing long jump accuracy in women (Kinesiology, 2020)
The purpose of this study was to determine whether the precision of verbal feedback affected the accuracy of standing long jump performance. Sixty-eight female participants (M age = 21.44 ± 1.01) were randomly assigned to two experimental groups. In total, each subject performed 9 jumps at three distances, i.e. 50 cm (3 trials), 75 cm (3 trials) and 100 cm (3 trials). Each group performed jumps in a reverse order. During the tasks, the study participants received verbal feedback at different levels of precision (no feedback; information that the jump was 'too far', 'too close' or 'correct'; information about the distance in centimetres). The results of statistical analysis indicated that the speed of changes in jump accuracy depended on the precision of verbal feedback. The difference between an actual jump result and a target result increased proportionally with jump length. With a large number of trials, verbal feedback accuracy does not affect the precision of women's long jump performance significantly. However, when high accuracy of task performance needs to be obtained quickly, feedback ought to define the exact difference between a target result and an actual jump result. The current findings also indicate that providing no feedback does not contribute to improving motor task performance accuracy.Keywords: auditory feedback, performance, knowledge of results, motor skills